IMPLEMENTASI KETERAMPILAN MENGELOLA KELAS MAHASISWA PENDIDIKAN BIOLOGI UNIVERSITAS TANJUNGPURA DALAM PRAKTIK MENGAJAR - Wahyuni, Eko Sri; Titin, Titin; Sandra, Klaudia Mareta (Universitas Tanjungpura, 2024)
Teachers play an important role in the development of students' potential and abilities through their responsibilities as professional educators. The success of teaching depends on the teacher's teaching skills. This study aims to describe the classroom management skills of fourth semester Biology Education A2 class FKIP Tanjungpura University academic year 2023/2024. Data were collected quantitatively through observation of 25 learning videos using a checklist table. The results showed the percentage of components of classroom management skills including responsiveness (96%), dividing attention (88%), focusing group attention (88%), giving clear instructions (100%), providing reinforcement (100%), modifying behavior (96%), group management (88%), finding and solving behavior that causes problems (4%), and reprimanding (4%). Of the nine components of classroom management skills, seven were rated excellent and two were rated deficient. Although the majority of skills were rated as excellent, there are some aspects that still need improvement. Keywords: Skills, Components, Classroom Management.